Adjektiva Bahasa Julu - Cindi Widarti Riskiana; Rostina Taib; Armia Armia (JIM Pendididikan Bahasa dan Sastra Indonesia, 2021)
This research is entitled "Julu Adjective Language". The formulation of the problem of this research (1) is how the Julu language adjectives are in the form of words. (2) What is the adjective Julu language in the form of phrases. The research objectives (1) describe the Julu language adjectives in word form. (2) Describe the adjectives in the form of phrases. The data in this study are Julu language adjectives. The methods and data collection techniques of this study are through listening techniques, interview techniques, note taking techniques, and introspection techniques. This research data processing technique selects and filters data, groups data, analyzes data, and concludes data. The results of this study (1) the adjective Julu language forms of basic words such as clean, fun, mende menahong, warm, and bergoh. In addition, the form of word compositions such as broadcast siew, ancestors ate, oda mesusun, and belen ate. (2) Julu language adjectives are in the form of phrases in the form 1). the pattern of combined free morphemes + free morphemes such as cemek su ‘sangat kotor’; 2). the pattern of combined free morphemes + free morphemes + bound morphemes such as cemek su ‘sangat kotor’ ; 3). the pattern of combined free morphemes + free morphemes + free morphemes + bound morphemes such as pate kelek engkus na ‘sangat wangi sekali’ ; 4). The shape of the pattern of free morpheme + bound morpheme + free morpheme such as mende na pate ‘cantik sekali’; 5). bound morpheme pattern + free morpheme + free morpheme + bound morpheme like the si pate mbereng na ‘yang hitam sekali’; 6). free morpheme pattern + compound words + bound morpheme like pate pinang masak na ‘orange sekali’; 7). The shape of the pattern of free morpheme + free morpheme + bound morpheme + free morpheme such as nggo pate desing na ‘sudah dekat sekali’; 8). The shape of the bound morpheme pattern + free morpheme + free morpheme + free morpheme such as tah bage tangis kade ‘ntah nangis seperti apa’; 9). form of free morpheme pattern + compound words + free morpheme like pate siar ate ku ‘kepingin sekali aku’ ; 10). Free morpheme + free morpheme + free morpheme forms such as ulang lolo su ‘jangan terlalu senang’ ; 11). The shape of the pattern of free morpheme + bound morpheme + free morpheme + bound morpheme like pate mo biar na ‘takut sekal’ ; 12). The shape of the bound morpheme pattern + free morpheme + free morpheme like yahh cilo su ‘yahh sangat terang’ ; 13). The shape of the bound morpheme pattern + free morpheme + free morpheme + free morpheme + bound morpheme like yahh pate nggo ndalit na ‘yahh sudah licin sekali’ ; and 14). The shape of the bound morpheme pattern + free morpheme + bound morpheme like si nipis na ‘yang tipisnya’.